24 h absorption and excretion profiles of cadmium from contaminated cooked brown rice and white rice in female rats. (November 2021) - Liu, Ruying; He, Qiang; Wu, Yue; Wang, Jinqiu; Fu, Jie
Abstract: The absorption and excretion of cadmium (Cd) in female rats fed with contaminated cooked brown rice (cBR) and cooked white rice (cWR) were evaluated in vivo for 24 h. Results showed that even when essential metals were abundant, the Cd absorption rate in the gastrointestinal (GI) tract of rats administered with cBR and cWR could reach >10% and >15% on average, respectively. When the body is under normal ionic state, Cd absorption was not disrupted by the amount of simultaneously ingested essential metal elements. The absorption segment of Cd was primarily in the duodenum. The Cd in the GI tract of cWR group had higher AUClast (2.02) than that of cBR group (1.44). Fecal excretion was the major route of Cd removal instead of urination. Approximately 15.00%–55.09% of the administered Cd was excreted via feces in the cBR group and 21.60%–27.38% in the cWR group. In summary, the cBR group had lower Cd absorption rate and AUClast value and higher Cd excretion rate than the cWR group. This study is helpful in implementing immediate interventions and determining the safety profiles of Cd in cooked rice matrix. Graphical abstract: Image 1 Highlights: The absorption rate of cadmium (Cd) in cooked rice group was >10%. The absorption segment of Cd in cooked rice groups was primarily in the duodenum. Cd had higher absorption in cooked white rice group than in cooked brown rice. Cd had higher excretion rate in cooked brown rice group than in cooked white rice.